LEADERS AND LEADERSHIP IN ORGANIZATIONS - Lubis, Lutfhia farhana; Hayati, Fitri (Journal of Educational Administration, 2023)
Leadership role in the community is very important in determining the direction of the management towards the achievement of a community/organization to achieve the vision. Shared equally by the members were in accordance with the planning step by step according to the function and role of the members work together towards the achievement of objectives. Leader of the organization/community with a variety of challenges in carrying out its functions, must have the knowledge and skills of planning, organizing, leading, controlling and empowering to know and understand how the resources are there, especially human resources. Style lead (leadership style) one skill that can determine the rhythm and direction of progress to be achieved, for example, patterns of behavior that are favored by the leader in directing and influencing the workers. The true leader is a person who has a different specificity with which ordinary people are able to look further, deeper, and wider.